2004
DOI: 10.1080/10425170400004104
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Analysis of Human Apg16L

Abstract: Autophagy is an intracellular bulk degradation system, which delivers cytoplasmic components to the lysosome/vacuole. In yeast and mammalian cells, the Apg12-Apg5 conjugate, together with Apg16, form a multimeric complex, which plays an essential role in autopihageosome formation. By large-scale sequencing analysis of a human fetal brain cDNA library, we isolated a cDNA encoding a putative protein with 607 amino acid residues, which shows 90% identity and 93% similarity to mouse Apg16L. This protein, designate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Autophagocytosis mediates bulk degradation of cytoplasmic components to the lysosome/vacuole. The process is involved in protein turnover, the starvation response, cellular differentiation, and cell death, but also in the processing of intracellular bacteria (33,34). How this process is implicated in susceptibility for CD remains elusive, although it would support the concept of CD being an inflammatory barrier disorder (35).…”
Section: Discussionmentioning
confidence: 98%
“…Autophagocytosis mediates bulk degradation of cytoplasmic components to the lysosome/vacuole. The process is involved in protein turnover, the starvation response, cellular differentiation, and cell death, but also in the processing of intracellular bacteria (33,34). How this process is implicated in susceptibility for CD remains elusive, although it would support the concept of CD being an inflammatory barrier disorder (35).…”
Section: Discussionmentioning
confidence: 98%
“…49 However, the exact molecular mechanism of ATG16L2 is still unclear. Previously, one study reported that the isoform ATG16L1 was essential for autophagy, while ATG16L2 did not seem to be important.…”
Section: Discussionmentioning
confidence: 99%
“…S1 A and B). The position of the Thr-to-Ala substitution in murine Atg16L1 varies depending on the splice isoform expressed: T300A (isoform β), T281A (isoform α), or T316A (isoform γ) (16). Murine isoform β is the equivalent of human isoform 1, so these mice are hereafter referred to as T300A mice.…”
Section: Resultsmentioning
confidence: 99%